2019
DOI: 10.1108/bfj-03-2018-0199
|View full text |Cite
|
Sign up to set email alerts
|

Exploring inside the box: a cross-cultural examination of stimuli affecting fast food addiction

Abstract: Purpose The purpose of this paper, a cross-cultural study, is twofold: first, to identify personal, social, demographical and marketing facets that imply fast food addiction in Pakistan and America, and second to explore the reasons of reduction in fast food consumption in Pakistan. Design/methodology/approach The present study followed an explanatory sequential mixed-methods research design. Both quantitative and qualitative data collection methods were used to obtain supportive results of fast food consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 73 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…Such personal opinions and beliefs include taste, convenience (Bianchi & Mortimer, 2015) and other hedonic components (Shahzad, Bilal, Xiao, & Yousaf, 2019). This is due to the fact that addiction is largely linked to individual impulse and affective characteristics especially among young consumers (Khalid, Nawaz, & Zahid, 2019). Indeed, food addiction is in itself a pathological and compulsive disorder in which consumer experience and strong hedonistic urges and cravings play a major role (Rosenbaum & Wong, 2012).…”
Section: Personal Factors and Addictionmentioning
confidence: 99%
“…Such personal opinions and beliefs include taste, convenience (Bianchi & Mortimer, 2015) and other hedonic components (Shahzad, Bilal, Xiao, & Yousaf, 2019). This is due to the fact that addiction is largely linked to individual impulse and affective characteristics especially among young consumers (Khalid, Nawaz, & Zahid, 2019). Indeed, food addiction is in itself a pathological and compulsive disorder in which consumer experience and strong hedonistic urges and cravings play a major role (Rosenbaum & Wong, 2012).…”
Section: Personal Factors and Addictionmentioning
confidence: 99%
“…FFA can be associated with health problems, including obesity, heart disease and digestive problems (Burmeister et al, 2013). Because FFA is a complex mental health issue that can harm well‐being, there is an immense need to effectively treat it (Khalid et al, 2019). However, shifting consumption to functional foods may not work because the taste and convenience of fast‐foods are so appealing (Ghoochani et al, 2018; Qin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that when consumers set boundaries to their eating habits it sometimes results in overeating (Ogden, 1994). According to Khalid et al (2019), while there is plenty of knowledge about consumer food‐related avoidance behaviour, marketing literature needs to update FFAC‐related research. Another question is how FFA can restrict binge eating to achieve consumer welfare (Burmeister et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among such approaches, there is the segmentation of consumers on the principle of intercultural unifying features. Tsiotsou, R.H. [2] testifies about examples of implementation of this approach in the sphere of tourism services provision. For the analysis, we used a quantitative method such as user ratings of hotels online on TripAdvisor.…”
Section: Discussionmentioning
confidence: 99%